Issues in excavating completely weathered granite for construction work at Labis, Johor [electronic resource] - Farah Shafiqah Mohd. Mazny, 1989-; Edy Tonnizam Mohamad (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2012